Hierarchical Core-sheath breathable textiles with absorption-dominated EMI shielding, strain-insensitive conductivity and efficient joule heating - Jian Zhang; Shasha Wang; Fengkai Zhou; Danna Zhou; Ziyue Zhu; Leqian Wei; Liqi Zhou; Mengqi Shan; Qian Zhang; Meiqi Hu; Guoping Guan; Fujun Wang; et al. (Chemical Engineering Journal, 2026)

Chemically induced proximity-driven dimerization of split Cas12a enables sensitive rapamycin detection in blood - Zhen Huang; Xiaowen Hu; Yajuan Zhou; Shanshan Zhang; Yao Zhao; Lei Xiong; Xuchun Han; Miaona Liu; Yao Hu; Yizhuo Zhang; Luqin Lv; Qiuxiang Cheng; et al. (Science Bulletin, 2026)

The role of heavy reflux in pressure swing adsorption for industrial carbon capture - Jinbiao Luo; Hao Yuan; Yalou Guo; Shuangjun Li; Qingchuan Chen; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

Fracture Development, Mechanisms, and Effectiveness in Tight Sandstone Reservoirs: Case Study of the Xujiahe Formation, Northeastern Sichuan Basin - Zhuoyi Li; Guoping Liu; Kewei Zu; Xing Zhang; Yunlong Xu; Chengxiang Wan; Jiasi Li; Xiaofei Zhao; Yuzhe Wang; Haoyu Wang; Tao Hu (Journal of Earth Science, 2026)

Wood taxonomic division and nutrient type jointly influence wood decomposition responses to nutrient additions in a subtropical forest - Xiangyu Ji; Lulu Ma; Shahla Hosseini Bai; Xian He; Zhiyuan Xu; Zhenyin Bai; Zhuqi Zhao; Guoping Zhao; Zhenhong Hu (Plant and Soil, 2026)

Pollen-based response patterns of vegetation dynamics to environmental changes during the early-mid Holocene in the Ningshao Plain, China - Zhen Li; Chunmei Ma; Zijing She; Haiyan Li; Konglan Shao; Bin Zhou; Zhujun Hu; Qing Yang; Guoping Sun; Michael Meadows; Hongbo Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Corrigendum to “Rapid and scalable synthesis of CALF-20 extrudates for VPSA-based CO2 capture” [Chem. Eng. J. 527 (2026) 171623] - Jifu Wang; Jianyu Sun; Lina Zhang; Guoping Hu; Gaobing Sheng; Keming Chen; Tianyang Zhu; Yufeng Hao; Hongyu Zhao; Baodeng Wang; Wei Wei; Nannan Sun (Chemical Engineering Journal, 2026)

Uncovering the role of Li+-H2O ion-dipole interaction in zeolite deactivation - Chenghao Liu; Yong Li; Zhe Lu; Shuzhuang Sun; Yong Wang; Zhifu Liu; Gang (Kevin) Li; Jingyue Shang; Songbai Hu; Lunhua He; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

miR-214-3p exacerbates mitochondrial dysfunction in parkinson's disease: a multi-omics and mechanistic study - Xinyu Wang; Dan Wang; Caiyun Zhang; Hongmei Zhang; Wenhui Wang; Wenxian Qian; Jin Zhou; Yunli Zhao; Jinghan Gao; Zheng Hu; Jiamin Qin; Zhizhong Wang; et al. (Experimental Brain Research, 2026)
Parkinson’s disease (PD) involves the loss of dopaminergic neurons, and prodromal PD exhibits elevated miR-214-3p, suggesting its role as a biomarker and pathogenic factor. This study investigated miR-214-3p’s effects on mitochondrial function in dopaminergic SH-SY5Y cells and mouse primary cortical neurons. In SH-SY5Y cells, proteomic/transcriptomic analyses and target prediction confirmed GFM1 as a direct target of miR-214-3p. miR-214-3p upregulation downregulated GFM1, causing severe mitochondrial bioenergetic impairment: increased reactive oxygen species (ROS), reduced oxygen consumption, diminished ATP production, and decreased respiratory chain complexes (RCC) I/IV expression. Critically, restoring GFM1 reversed these mitochondrial deficits and neuronal dysfunction. In mouse primary cortical neurons, miR-214-3p overexpression also impaired RCC I/IV but did not affect GFM1, revealing a cell type-dependent regulatory mechanism. These findings demonstrate that elevated miR-214-3p impairs mitochondrial function in a cell-specific manner. In dopaminergic cells, this damage is mediated by GFM1 downregulation, highlighting the miR-214-3p/GFM1 axis as a potential cell-type specific therapeutic target for PD and related dopaminergic neuronopathies.

Microbial biofilm-based hydrovoltaic system for degradating organic pollutants - Zihan Lin; Guoping Ren; Yuanhong Guo; Xiang Shen; Qichang Hu; Shungui Zhou (Water Research, 2026)

Bioengineering extracellular vesicles for enhanced therapeutic functionality and clinical potential in the cardiovascular system - Yongtao Wang; Meiyu Hu; Michail Spanos; Shihui Xu; Jiaxin Song; Guoping Li; Dragos Cretoiu; Junjie Xiao (Science Bulletin, 2026)

Combined aperture widening and strong polarization in Li+-exchanged mordenite for efficient direct air capture of CO2 - Zhifu Liu; Guanghui Shi; Shuzhuang Sun; Yong Wang; Jingyue Shang; Songbai Hu; Wenkang Deng; Chuhan Fu; Chenghao Liu; Xiao Wang; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

Rapid and scalable synthesis of CALF-20 extrudates for VPSA-based CO2 capture - Jifu Wang; Jianyu Sun; Lina Zhang; Guoping Hu; Gaobing Sheng; Keming Chen; Tianyang Zhu; Yufeng Hao; Hongyu Zhao; Baodeng Wang; Wei Wei; Nannan Sun (Chemical Engineering Journal, 2026)

Regulation of Melatonin on AQP4 Expression in Brain of SD Newborn Rats with Bilirubin Encephalopathy and Protection Mechanism - Kaige Xue; Xuefeng Cheng; Weijian Qian; Hemant Mistry; Ping Fan; Jiaheng Hu; Chunyan Chen; Lirong Zhang; Parisa Vazirinasab; Juan Huang; Weitian Lu; Jin Xu; et al. (Molecular Neurobiology, 2026)

Role of the AMPK/PGC-1α/SIRT3-Mediated Mitochondrial Dysfunction in the Neurotoxicity of Methanol - Xiaojie Han; Mengnan Peng; Xinqiao Wang; Yundi Hu; Guoping Li; Yanan Song; Yanling Lv; Nan Chen (Molecular Neurobiology, 2026)

Compositional convergence of dissolved organic matter from root litter to rhizosphere soil in a semiarid grassland of North China - Xiaohan Mo; Zongxiao Zhang; Mengke Wang; Qiang Zhang; Guodong Sun; Weifeng Hu; Guoping Chen; Deliang Kong; Chengcheng Dong; Hui Zeng; Junjian Wang (Organic Geochemistry, 2025)

Volatile markers as indicators of salmon freshness states identified via volatolomics and machine learning - Qian Hu; Bingwu Zhou; Guoping Li; Ranran Xing; Ying Chen; Jiukai Zhang (Food Research International, 2025)

Highly efficient biophotoelectrochemical methanogenesis coupling with water sterilization via robust interfacial electronic communication - Jing Hu; Chaohui Yang; Yaping Qi; Mingqiu Hong; Jiajing Chen; Guoping Ren; Jie Ye (Chemical Engineering Journal, 2025)

Urban trash bins as reservoirs of multidrug-resistant Enterococcus with shared resistance genes across clinical and environmental niches - Jie Li; Xiaorui Mao; Yu Song; Xiaohe Hu; Guoping Zhao; Biao Tang (Journal of Hazardous Materials, 2025)

Dynamically programmable plant-derived scaffold coordinates alveolar bone repair cascade: Phase-adaptive integration from hemostasis to bone remodeling - Yeke Chen; Yumei Ning; Fang Dai; Yuting Yang; Chenjiang He; Kaiqiang Yang; Yichen Hu; Guoping Cheng; Li Song (Chemical Engineering Journal, 2025)

Combined influence of strong winds and warm deep water on the formation of Amundsen Sea Polynya in winter - Mengting Zhuo; Yu Hong; Yuhong Zhang; Jiping Liu; Lingqiao Cheng; Guoping Zhu; Song Hu; Yan Du (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Enhanced deep denitrification for high-salinity wastewater treatment by constructing biofilm-based technology - Kun Ding; Shan Yang; Hao Hu; Zhenghao Li; Haoran Duan; Xiaoqiang Chen; Yankun Liu; Guoping Sheng (Journal of Environmental Management, 2025)

Wood-inhabiting fungal community characteristics responses to nutrient additions vary among tree taxonomic groups - Xian He; Teng Yang; Katja T. Rinne-Garmston; Xiangyu Ji; Qian Xu; Zhiyuan Xu; Yuxiong Zheng; Zhuqi Zhao; Guoping Zhao; Zhenhong Hu (Journal of Soils and Sediments, 2025)

Mycorrhizal dominance influences tree species richness and richness–biomass relationship in China's forests - Suhui Ma; Guoping Chen; Qiong Cai; Chengjun Ji; Biao Zhu; Zhiyao Tang; Shuijin Hu; Jingyun Fang (Ecology, 2025)
Mycorrhizal associations drive plant community diversity and ecosystem functions. Arbuscular mycorrhiza (AM) and ectomycorrhiza (EcM) are two widespread mycorrhizal types and are thought to differentially affect plant diversity and productivity by nutrient acquisition and plant–soil feedback. However, it remains unclear how the mixture of two mycorrhizal types influences tree diversity, forest biomass, and their relationship at large spatial scales. Here, we explored these issues using data from 1247 plots (600 m 2 for each) across China's natural forests located mostly in temperate and subtropical regions. Both AM‐dominated and EcM‐dominated forests show relatively lower tree species richness and stand biomass, whereas forests with the mixture of mycorrhizal strategies sustain more tree species and higher biomass. Interestingly, the positive effect of tree diversity on biomass is stronger in forests with low (≤50%) than high AM tree proportion (>50%), reflecting a shift from the complementarity effect to functional redundancy with increasing AM trees. Our findings suggest that mycorrhizal dominance influences tree diversity and richness–biomass relationship in forest ecosystems.

The knockout of SlMTC impacts tomato seed size and reduces resistance to salt stress in tomato - Zihan Gao; Qingling Yang; Hui Shen; Pengyu Guo; Qiaoli Xie; Guoping Chen; Zongli Hu (Plant Science, 2024)

qSCR4.05 and qSCR4.08, two QTLs on chromosome 4 are associated with resistance to southern corn rust in maize - Junying Liu; Xiaoming Wang; Chenping Hou; Mingjian Hu; Wenjie Du; Pengfei Sun; Zhuangzhuang Dai; Xingchuan Wang; Ruijie Chen; Fei Gao; Guoping Shu; Yibo Wang; et al. (Physiological and Molecular Plant Pathology, 2024)

Fe-mordenite for high-performance N2 rejection - Zhi Yu; Jianing Yang; Seyed Hesam Mousavi; Penny Xiao; Xue Yan; Ali Zavabeti; Yongqiang Wang; Kaifei Chen; Zhe Jefferson Liu; Guoping Hu; Xiaoling Liu; Yu Zhou; et al. (Chemical Engineering Journal, 2024)

Early-mid Holocene vegetation and diversity evolution on the Ningshao Plain, eastern China - Zhen Li; Chunmei Ma; Yufan Ni; Zeyu Liu; Bingling Wang; Zhujun Hu; Guoping Sun; Yonglei Wang; Michael Meadows; Hongbo Zheng (CATENA, 2024)

Impact of diatomit on the transport behavior of unmodified and carboxyl-modified nanoplastics in saturated porous media - Yuheng Wu; Ming Wu; Zhou Cheng; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu; Guoping Lu (Environmental Pollution, 2024)

Sustainable finance in natural resource extraction: Navigating green recovery pathways - Bangyong Hu; Nianjiao Peng; Guoping Zhu (Resources Policy, 2024)

Improving Granulosa Cell Function in Premature Ovarian Failure with Umbilical Cord Mesenchymal Stromal Cell Exosome-Derived hsa_circ_0002021 - Ge Yang; Bo Zhang; Mei Xu; MingJun Wu; Jie Lin; ZiYu Luo; YueHua Chen; Qin Hu; GuoPing Huang; HaiYan Hu (Tissue Engineering and Regenerative Medicine, 2024)

Significance of non-DLVO interactions on the co-transport of levofloxacin and titanium dioxide nanoparticles in porous media - Yiqun Cui; Ming Wu; Guoping Lu; Zhou Cheng; Meng Chen; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Environmental Pollution, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

CO2 capture using low silica X zeolite synthesized from low-grade coal gangue via a two-step activation method - Chenghao Liu; Fu Rao; Yalou Guo; Zhe Lu; Wenkang Deng; Guobiao Li; Hui Zhang; Tao Qi; Guoping Hu (Journal of Environmental Chemical Engineering, 2024)

Structural Control of the Getang Carlin-Type Gold Deposit in Southwest China - Guoping Zeng; Xinlu Hu; Diwei Luo; Jianzhong Liu; Shuzhen Yao; Yongjie Jin (Journal of Earth Science, 2024)

Unique ternary Pd/NH2-MIL-125/CdIn2S4 composite expands the absorption range of visible light and improves H2 evolution efficiency - Man Zhang; Kangzheng Li; Zhe Yin; Zhichao Zhang; Qingcheng Luo; Binglin Tang; Guoping Yu; Tianding Hu; Shaoyun Shan (Journal of Environmental Chemical Engineering, 2024)

Overexpression of SlCRF6 in tomato inhibits leaf development and affects plant morphology - Changguang Liao; Hui Shen; Zihan Gao; Yunshu Wang; Zhiguo Zhu; Qiaoli Xie; Ting Wu; Guoping Chen; Zongli Hu (Plant Science, 2024)

Quantification and visualization of groundwater contamination prevention regionalization based on analytic hierarchy process method (AHP) in Guangdong-Hong Kong-Macao Greater Bay Area, South China - Zhou Cheng; Guoping Lu; Ming Wu; Zhaohui Li; Yirong Deng; Jinzhe Wu; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Journal of Hydrology, 2024)

Efficient self-cleaning and antibacterial ceramics with ultra-low doping and high exposure of silver - Kaibo Hu; Chuanqi Zhang; Guobiao Li; Yucheng Liu; Dong Wang; Ke Li; Guoping Hu; Liuyimei Yang; Yinhua Wan (Journal of Hazardous Materials, 2024)

Integrating ecosystem services closely related to human well-being into the restoration and management of deep lakes facing multiple stressors: Lessons from long-term practice in Qiandao Lake, China - Zhen Zhang; Qigen Liu; Guoping Gao; Jianqiang Shao; Jiayong Pan; Guangxi He; Zhongjun Hu (Science of The Total Environment, 2023)

Overexpression of SlPRE3 alters the plant morphologies in Solanum lycopersicum - Pengyu Guo; Qingling Yang; Yunshu Wang; Zhijie Yang; Qiaoli Xie; Guoping Chen; Xuqing Chen; Zongli Hu (Plant Cell Reports, 2023)

Quantification of two-site kinetic transport parameters of polystyrene nanoplastics in porous media - Yuheng Wu; Zhou Cheng; Ming Wu; Yanru Hao; Guoping Lu; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Chemosphere, 2023)

Dopamine/β-cyclodextrin synergistically modified core-shell MF@ZIF-8 porous membrane for high-efficient filtering of particulate matter (PM) in air and gathering oil in water - Zerong He; Nan Hu; Xiaoyun Meng; Jiang Li; Qi Wu; Guoping Yang; Wenyan Zhang; Yaoyu Wang (Chemical Engineering Journal, 2023)

The dysregulation of miRNAs in epilepsy and their regulatory role in inflammation and apoptosis - Guoping Xie; Huan Chen; Chan He; Siheng Hu; Xue Xiao; Qunying Luo (Functional & Integrative Genomics, 2023)
Epilepsy is a neurological disorder that impacts millions of people worldwide, and it is characterized by the occurrence of recurrent seizures. The pathogenesis of epilepsy is complex, involving dysregulation of various genes and signaling pathways. MicroRNAs (miRNAs) are a group of small non-coding RNAs that play a vital role in the regulation of gene expression. They have been found to be involved in the pathogenesis of epilepsy, acting as key regulators of neuronal excitability and synaptic plasticity. In recent years, there has been a growing interest in exploring the miRNA regulatory network in epilepsy. This review summarizes the current knowledge of the regulatory miRNAs involved in inflammation and apoptosis in epilepsy and discusses its potential as a new avenue for developing targeted therapies for the treatment of epilepsy.

Regulatory miRNAs, circRNAs and lncRNAs in cell cycle progression of breast cancer - Huan Chen; Guoping Xie; Qunying Luo; Yisha Yang; Siheng Hu (Functional & Integrative Genomics, 2023)

Important effects of polypropylene on migration of ciprofloxacin in groundwater - Yanna Chen; Cehui Mo; Ming Wu; Yanru Hao; Zhou Cheng; Guoping Lu; Qusheng Li; Bill X. Hu; Jianfeng Wu; Jichun Wu (Journal of Environmental Chemical Engineering, 2023)

Oxidative lipidomics to elucidate the non-volatile derivatives of four typical triglycerides in vegetable oils under simulated frying conditions - Qian Hu; Jiukai Zhang; Guoping Li; Liyang Wei; Chenchun Zhong; Ying Chen (Food Chemistry, 2023)

Genomic insights into the genetic basis of cotton breeding in China - Yiqian Li; Zhanfeng Si; Guoping Wang; Zhuolin Shi; Jinwen Chen; Guoan Qi; Shangkun Jin; Zegang Han; Wenhao Gao; Yue Tian; Yun Mao; Lei Fang; et al. (Molecular Plant, 2023)

Pyridine N of N/Co-co-doped graphite gas diffusion electrode facilitating the efficient production of hydroxyl radicals in the electro-peroxone process - Qiang Bi; Sisi Jiang; Changfeng Hu; Li Zhang; Yilin Zhao; Bo Yang; Guoping Li; Juanqin Xue (Journal of Environmental Chemical Engineering, 2023)

SlERF.J2 reduces chlorophyll accumulation and inhibits chloroplast biogenesis and development in tomato leaves - Yanan Chen; Xi Cai; Boyan Tang; Qiaoli Xie; Guoping Chen; Xuqing Chen; Zongli Hu (Plant Science, 2023)

Hygroelectric-photovoltaic coupling generator using self-assembled bio-nano hybrids - Qichang Hu; Guoping Ren; Jie Ye; Bintian Zhang; Christopher Rensing; Shungui Zhou (Chemical Engineering Journal, 2023)

Anthocyanin accumulation and transcriptional regulation in purple flowering stalk (Brassica campestris L. var. purpurea Bailey) - Pengyu Guo; Bin Zhang; Zongli Hu; Shuang Zhou; Yunshu Wang; Qiaoli Xie; Guoping Chen (Plant Molecular Biology, 2023)

The AP2/ERF transcription factor SlERF.J2 functions in hypocotyl elongation and plant height in tomato - Yanan Chen; Hong Yang; Boyan Tang; Fenfen Li; Qiaoli Xie; Guoping Chen; Zongli Hu (Plant Cell Reports, 2022)

The role of melatonin in tomato stress response, growth and development - Qiaoli Xie; Yu Zhang; Yingxia Cheng; Yanling Tian; Junjie Luo; Zongli Hu; Guoping Chen (Plant Cell Reports, 2022)

The AP2/ERF transcription factor SlERF.F5 functions in leaf senescence in tomato - Yanan Chen; Panpan Feng; Boyan Tang; Zongli Hu; Qiaoli Xie; Shuang Zhou; Guoping Chen (Plant Cell Reports, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Do the performance and efficiency of China’s carbon emission trading market change over time? - Shiyi Zhang; Kai Jiang; Lan Wang; Geoff Bongers; Guoping Hu; Jia Li (Environmental Science and Pollution Research, 2020)

Silencing of the MADS-Box Gene SlMADS83 Enhances Adventitious Root Formation in Tomato Plants - Anzhou Li; Guoping Chen; Yunshu Wang; Honglian Liang; Zongli Hu (Journal of Plant Growth Regulation, 2020)

The bHLH transcription factor SlPRE2 regulates tomato fruit development and modulates plant response to gibberellin - Zhiguo Zhu; Honglian Liang; Guoping Chen; Fenfen Li; Yunshu Wang; Changguang Liao; Zongli Hu (Plant Cell Reports, 2019)

The tomato MADS-box gene SlMBP9 negatively regulates lateral root formation and apical dominance by reducing auxin biosynthesis and transport - Anzhou Li; Guoping Chen; Xiaohui Yu; Zhiguo Zhu; Lincheng Zhang; Shengen Zhou; Zongli Hu (Plant Cell Reports, 2019)

Wild barley shows a wider diversity in genes regulating heading date compared with cultivated barley - Hongliang Hu; Ibrahim Ahmed; Shormin Choudhury; Yun Fan; Sergey Shabala; Guoping Zhang; Matthew Harrison; Holger Meinke; Meixue Zhou (Euphytica, 2019)

SlHDA5, a Tomato Histone Deacetylase Gene, Is Involved in Responding to Salt, Drought, and ABA - Xiaohui Yu; Qiong Gao; Guoping Chen; Jun-E Guo; Xuhu Guo; Boyan Tang; Zongli Hu (Plant Molecular Biology Reporter, 2018)

A histone deacetylase gene, SlHDA3, acts as a negative regulator of fruit ripening and carotenoid accumulation - Jun-E Guo; Zongli Hu; Xiaohui Yu; Anzhou Li; Fenfen Li; Yunshu Wang; Shibing Tian; Guoping Chen (Plant Cell Reports, 2018)

Silencing of SlHB2 Improves Drought, Salt Stress Tolerance, and Induces Stress-Related Gene Expression in Tomato - Jingtao Hu; Guoping Chen; Wencheng Yin; Baolu Cui; Xiaohui Yu; Yu Lu; Zongli Hu (Journal of Plant Growth Regulation, 2017)

Molecular Characterization of Nine Tissue-Specific or Stress-Responsive Genes of Histone Deacetylase in Tomato (Solanum lycopersicum) - Jun-E Guo; Zongli Hu; Xuhu Guo; Lincheng Zhang; Xiaohui Yu; Shengen Zhou; Guoping Chen (Journal of Plant Growth Regulation, 2017)

Bisphenol A Represses Dopaminergic Neuron Differentiation from Human Embryonic Stem Cells through Downregulating the Expression of Insulin-like Growth Factor 1 - Boxian Huang; Song Ning; Qinjing Zhang; Aiqin Chen; Chunyan Jiang; Yugui Cui; Jian Hu; Hong Li; Guoping Fan; Lianju Qin; Jiayin Liu (Molecular Neurobiology, 2017)

Silencing SlAGL6, a tomato AGAMOUS-LIKE6 lineage gene, generates fused sepal and green petal - Xiaohui Yu; Guoping Chen; Xuhu Guo; Yu Lu; Jianling Zhang; Jingtao Hu; Shibing Tian; Zongli Hu (Plant Cell Reports, 2017)

The abiotic stress-responsive NAC transcription factor SlNAC11 is involved in drought and salt response in tomato (Solanum lycopersicum L.) - Lingling Wang; Zongli Hu; Mingku Zhu; Zhiguo Zhu; Jingtao Hu; Ghulam Qanmber; Guoping Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Identification of a divergent variant of grapevine berry inner necrosis virus in grapevines showing chlorotic mottling and ring spot symptoms - Xudong Fan; Ni Hong; Zunping Zhang; Zuokun Yang; Fang Ren; Guojun Hu; Zhengnan Li; Jun Zhou; Yafeng Dong; Guoping Wang (Archives of Virology, 2016)

Distribution characteristics and source apportionment of polycyclic aromatic hydrocarbons (PAHs) in the Liao River drainage basin, northeast China - Jian Hu; Congqiang Liu; Guoping Zhang; Yanlin Zhang; Siliang Li; Zhiqi Zhao; Baojian Liu; Qinjun Guo (Environmental Monitoring and Assessment, 2016)

Genome-wide identification of phosphate-deficiency-responsive genes in soybean roots by high-throughput sequencing - Houqing Zeng; Guoping Wang; Yuqi Zhang; Xiaoyan Hu; Erxu Pi; Yiyong Zhu; Huizhong Wang; Liqun Du (Plant and Soil, 2016)

MicroRNA let-7e Is a Potential Circulating Biomarker of Acute Stage Ischemic Stroke - Guoping Peng; Yuan Yuan; Shanshan Wu; Fangping He; Yewen Hu; Benyan Luo (Translational Stroke Research, 2015)

Identification of QTLs associated with haze active proteins in barley - Lingzhen Ye; Yuqing Huang; Hongliang Hu; Fei Dai; Guoping Zhang (Euphytica, 2015)

Assessment of the Altitudinal Atmospheric Metal(loid) Deposition in a Mountainous City by Mosses - Haixia Li; Guoping Zhang; Hong Liu; Ling Li; Zhiping Fu; Xiaoxue Ouyang; Jingjing Chen; Jian Hu (Bulletin of Environmental Contamination and Toxicology, 2015)

Genetic diversity and recombination analysis of grapevine leafroll-associated virus 1 from China - Xudong Fan; Ni Hong; Yafeng Dong; Yanxia Ma; Zun Ping Zhang; Fang Ren; Guojun Hu; Jun Zhou; Guoping Wang (Archives of Virology, 2015)

QTL analysis of three flower-related traits based on an interspecific genetic map of Luffa - Junjie Cui; Jiaowen Cheng; Guoping Wang; Xin Tang; Zhiming Wu; Mingbao Lin; Lianfang Li; Kailin Hu (Euphytica, 2015)

Identification and expression analyses of calmodulin-binding transcription activator genes in soybean - Guoping Wang; Houqing Zeng; Xiaoyan Hu; Yiyong Zhu; Yang Chen; Chenjia Shen; Huizhong Wang; B. W. Poovaiah; Liqun Du (Plant and Soil, 2015)

Tomato lipoxygenase D involved in the biosynthesis of jasmonic acid and tolerance to abiotic and biotic stress in tomato - Tingzhang Hu; Zongli Hu; Hua Zeng; Xiaoxiao Qv; Guoping Chen (Plant Biotechnology Reports, 2015)

Heterologous Expression of BoPAP1 in Tomato Induces Stamen Specific Anthocyanin Accumulation and Enhances Tolerance to a Long-Term Low Temperature Stress - Lijun Ren; Zongli Hu; Yali Li; Bin Zhang; Yanjie Zhang; Yun Tu; Guoping Chen (Journal of Plant Growth Regulation, 2014)

Molecular Characterization of Six Tissue-Specific or Stress-Inducible Genes of NAC Transcription Factor Family in Tomato (Solanum lycopersicum) - Mingku Zhu; Zongli Hu; Shuang Zhou; Lingling Wang; Tingting Dong; Yu Pan; Guoping Chen (Journal of Plant Growth Regulation, 2014)

The abiotic stress-responsive NAC-type transcription factor SlNAC4 regulates salt and drought tolerance and stress-related genes in tomato (Solanum lycopersicum) - Mingku Zhu; Guoping Chen; Jianling Zhang; Yanjie Zhang; Qiaoli Xie; Zhiping Zhao; Yu Pan; Zongli Hu (Plant Cell Reports, 2014)

Role of microRNAs in plant responses to nutrient stress - Houqing Zeng; Guoping Wang; Xiaoyan Hu; Huizhong Wang; Liqun Du; Yiyong Zhu (Plant and Soil, 2014)

Flocculation and particle size analysis of expansive clay sediments affected by biological, chemical, and hydrodynamic factors - Xiaoling Tan; Liming Hu; Allen H. Reed; Yoko Furukawa; Guoping Zhang (Ocean Dynamics, 2014)

Overexpression of the Tomato 13-Lipoxygenase Gene TomloxD Increases Generation of Endogenous Jasmonic Acid and Resistance to Cladosporium fulvum and High Temperature - Tingzhang Hu; Hua Zeng; Zongli Hu; Xiaoxiao Qv; Guoping Chen (Plant Molecular Biology Reporter, 2013)

An ethylene response factor (ERF5) promoting adaptation to drought and salt tolerance in tomato - Yu Pan; Graham B. Seymour; Chungui Lu; Zongli Hu; Xuqing Chen; Guoping Chen (Plant Cell Reports, 2012)

A putative functional MYB transcription factor induced by low temperature regulates anthocyanin biosynthesis in purple kale (Brassica Oleracea var. acephala f. tricolor) - Bin Zhang; Zongli Hu; Yanjie Zhang; Yali Li; Shuang Zhou; Guoping Chen (Plant Cell Reports, 2012)

Molecular characterization and functional analysis by heterologous expression in E. coli under diverse abiotic stresses for OsLEA5, the atypical hydrophobic LEA protein from Oryza sativa L. - Shuai He; Lili Tan; Zongli Hu; Guoping Chen; Guixue Wang; Tingzhang Hu (Molecular Genetics and Genomics, 2012)

Molecular and serological diversity in Apple chlorotic leaf spot virus from sand pear (Pyrus pyrifolia) in China - Yansu Song; Ni Hong; Liping Wang; Hongju Hu; Rui Tian; Wenxing Xu; Fang Ding; Guoping Wang (European Journal of Plant Pathology, 2011)

Functional analysis of tomato LeEIL1 in an Arabidopsis ein2 mutant - Yu Pan; Guoping Chen; Chungui Lu; Xuqing Chen; Zongli Hu (Acta Physiologiae Plantarum, 2011)

Heterologous synthesis and assembly of functional LHII antenna complexes from Rhodovulum sulfidophilum in Rhodobacter sphaeroides mutant - Wanneng Wang; Zongli Hu; Xuqing Chen; Zhiping Zhao; Jinzhe Li; Guoping Chen (Molecular Biology Reports, 2009)